A Novel Class of Potent Anti-Tyrosinase Compounds with Antioxidant Activity, 2-(Substituted phenyl)-5-(trifluoromethyl)benzo[d]thiazoles: In Vitro and In Silico Insights - YeJi Hwang; Jieun Lee; Hee Jin Jung; Sultan Ullah; Jeongin Ko; Yeongmu Jeong; Yu Jung Park; Min Kyung Kang; Hwayoung Yun; Min-Soo Kim; Pusoon Chun; Hae Young Chung; et al. (MDPI AG, 2022)
Sixteen compounds bearing a benzothiazole moiety were synthesized as potential tyrosinase inhibitors and evaluated for mushroom tyrosinase inhibitory activity. The compound 4-(5-(trifluoromethyl)benzo[d]thiazol-2-yl)benzene-1,3-diol (compound 1b) exhibited the highest tyrosinase activity inhibition, with an IC50 value of 0.2 ± 0.01 μM (a potency 55-fold greater than kojic acid). In silico results using mushroom tyrosinase and human tyrosinase showed that the 2,4-hydroxyl substituents on the phenyl ring of 1b played an important role in the inhibition of both tyrosinases. Kinetic studies on mushroom tyrosinase indicated that 1b is a competitive inhibitor of monophenolase and diphenolase, and this was supported by docking results. In B16F10 murine melanoma cells, 1a and 1b dose-dependently and significantly inhibited melanin production intracellularly, and melanin release into medium more strongly than kojic acid, and these effects were attributed to the inhibition of cellular tyrosinase. Furthermore, the inhibition of melanin production by 1b was found to be partially due to the inhibition of tyrosinase glycosylation and the suppression of melanogenesis-associated genes. Compound 1c, which has a catechol group, exhibited potent antioxidant activities against ROS, DPPH, and ABTS, and 1b also had strong ROS and ABTS radical scavenging activities. These results suggest that 5-(trifluoromethyl)benzothiazole derivatives are promising anti-tyrosinase lead compounds with potent antioxidant effects.